Effect of Sishen Pill on Memory T Cells From Experimental Colitis Induced by Dextran Sulfate Sodium - Ge, Wei; Wang, Hai-Yan; Zhao, Hai-Mei; Liu, Xue-Ke; Zhong, You-Bao; Long, Jian; Zuo, Zheng-Yun; Liu, Duan-Yong (Frontiers in Pharmacology, 2020)
Immune memory has a protective effect on the human body, but abnormal immune memory is closely related to the occurrence and development of autoimmune diseases including inflammatory bowel disease (IBD). Sishen Pill (SSP) is a classic prescription of traditional Chinese medicine, which is often used to treat chronic colitis, but it is not clear whether SSP can alleviate experimental colitis by remodeling immune memory. In the present study, the therapeutic effect of SSP on chronic colitis induced by dextran dextran (DSS) was evaluated by colonic length, colonic weight index, macroscopic and microscopic scores, and pathological observation. The cytokines levels were tested by enzyme-linked immunosorbent assay (ELISA); the percentage of central memory T (Tcm) and effector memory T (Tem) cells were analyzed by flow cytometry; and activation of phosphoinositide 3-kinase (PI3K)/Akt signaling proteins was measured by western blotting. After 7-days’ treatment, SSP alleviated DSS-induced colitis, which was demonstrated by decreased colonic weight index, colonic weight, histopathological injury scores, restored colonic length, gradual recovery of colonic colonic mucosa, and lower levels of interleukin (IL)-2, IL-7, IL-12 and IL-15, while SSP increased IL-10 expression. SSP obviously regulated the quantity and subpopulation of Tcm and Tem cells. Furthermore, SSP markedly inhibited activation of PI3K, Akt, phospho-Akt, Id2, T-bet, forkhead box O3a, Noxa and C-myc proteins in the PI3K/Akt signaling pathway, and activated Rictor, Raptor, tuberous sclerosis complex (TSC)1, TSC2, phospho-AMP-activated kinase (AMPK)-α, AMPK-α, eukaryotic translation initiation factor 4E-binding protein 2, kinesin family member 2a and 70-kDa ribosomal protein S6 kinase. These results indicate that SSP effectively controls Tem cells to relieve experimental colitis induced by DSS via the PI3K/Akt signaling pathway.